LEGAL COUNSELING BY A NOTARY AS A MEANS TO PRODUCE A BALANCED AGREEMENT - Hatta Isnaini Wahyu Utomo (NOTARIIL Jurnal Kenotariatan, 2022)
The Law on Notary Position authorizes Notaries to provide legal advice to parties related to deeds. Through this legal counselling, it is hoped that conflicts can be avoided in the future. This study analyzes the benefits of legal counselling provided by a notary. The research method used is normative legal research using a statutory approach and a conceptual approach. The results show that the notary public has the authority to provide legal counselling to parties related to deed making, especially those related to agreements. The role of the notary, in this case, is to provide counselling so that the agreement made by the parties is balanced and the parties understand their respective rights and obligations.